Investigation of wind actions on core-walls in high-rise buildings - Ong, Jing Yuan (2015)
The objective of this report is to study the wind effects on the design of a lateral load resisting system reinforced concrete (RC) core-wall in high-rise buildings both analytically and numerically. A numerical model was constructed with the aid of commercial software ETABS. The prototype building with a central core-wall is investigated using different numbers of storeys, namely 20, 40, and 60, with the corresponding building heights varied from 60m to 180m. The dimensions of core-walls, positions of core-wall, and building aspect ratio of the building are varied accordingly to analyze the effects on the core-wall and the whole structure. The parameters discussed in this report include the ultimate overturning moment of the core-wall at the ground, lateral shear force, diaphragm drift of the core-wall and storey drift.